2018
DOI: 10.1158/0008-5472.can-17-2892
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A Function in Mammary Epithelium Impacts Jak2/Stat5 Signaling, Morphogenesis, Differentiation, and Tumorigenesis in the Mammary Gland

Abstract: The prolyl isomerase cyclophilin A (CypA) regulates the Jak2/Stat5 pathway, which is necessary for mammary differentiation and the pathogenesis of breast cancer. In this study, we assessed the role of this isomerase during mammary gland development and erbB2-driven tumorigenesis. Genetic deletion of CypA resulted in delayed mammary gland morphogenesis and differentiation with corresponding decrease in Jak2/Stat5 activation; mammary gland cross-transplantation confirmed this defect was epithelial in nature. Ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Peptidylprolyl isomerase A as one of the most abundant members of cyclophilin (Cyp) family proteins has been reported upregulated in breast cancer ( Volker et al, 2018 ), esophageal cancer ( Qi et al, 2008 ), small cell lung cancer ( Campa et al, 2003 ), colorectal cancer ( Wong et al, 2008 ), pancreatic cancer ( Li et al, 2013 ), melanoma ( Caputo et al, 2011 ), malignant glioblastoma ( Sun et al, 2011 ; Saw et al, 2018 ), serous ovarian cancer ( Qi et al, 2019 ), and skin cancer ( Han et al, 2012 ). Cyps possess a peptidyl prolyl isomerase (PPIase), catalyzing the conversion between cis-trans isomers of proline on the peptide ( Lee, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peptidylprolyl isomerase A as one of the most abundant members of cyclophilin (Cyp) family proteins has been reported upregulated in breast cancer ( Volker et al, 2018 ), esophageal cancer ( Qi et al, 2008 ), small cell lung cancer ( Campa et al, 2003 ), colorectal cancer ( Wong et al, 2008 ), pancreatic cancer ( Li et al, 2013 ), melanoma ( Caputo et al, 2011 ), malignant glioblastoma ( Sun et al, 2011 ; Saw et al, 2018 ), serous ovarian cancer ( Qi et al, 2019 ), and skin cancer ( Han et al, 2012 ). Cyps possess a peptidyl prolyl isomerase (PPIase), catalyzing the conversion between cis-trans isomers of proline on the peptide ( Lee, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding tumor development, Volker et al (Volker et al, 2018) showed that Cyps promote mammary tumorigenesis in mice. In a non-small cell lung cancer murine model, overexpression of Cyps elevated tumor metastasis rate compared to those with downregulated Cyps (Guo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This would argue that NIM811 affects metastatic outgrowth, but does not alter micro-metastatic seeding, and further studies are planned to examine the mechanistic basis for this effect. Significant alterations in mammary cancer progression were also observed in the PyMT spontaneous model ( Volker et al., 2018 ). CypA −/- × PyMT mice demonstrated a highly significant decrease in tumor burden in comparison with the CypA +/+ × PyMT cohorts ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 93%